2017
DOI: 10.1111/trf.14326
|View full text |Cite
|
Sign up to set email alerts
|

Successful kidney transplantation in a patient with congenital thrombotic thrombocytopenic purpura (Upshaw‐Schulman syndrome)

Abstract: Our experience suggests that kidney transplantation may be an appropriate management for carefully selected patients with congenital TTP who develop end-stage renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Though analysis by bioinformatic tools is inconsistent (Mutation Taster: polymorphism; PolyPhen2: probably damaging; SIFT: tolerated; PROVEAN: deleterious), a biological consequence of c.2746C>T, p.Arg916Cys is plausible as it creates an unpaired cysteine. More importantly, it was reported in compound heterozygosity with a further ADAMTS13 mutation in several Upshaw-Schulman syndrome (USS) patients (15)(16)(17). Furthermore, a poster presented by Russo et al (18), reported an USS patient with homozygosity for the same complex allele as found in the patient described here.…”
Section: Discussionsupporting
confidence: 64%
“…Though analysis by bioinformatic tools is inconsistent (Mutation Taster: polymorphism; PolyPhen2: probably damaging; SIFT: tolerated; PROVEAN: deleterious), a biological consequence of c.2746C>T, p.Arg916Cys is plausible as it creates an unpaired cysteine. More importantly, it was reported in compound heterozygosity with a further ADAMTS13 mutation in several Upshaw-Schulman syndrome (USS) patients (15)(16)(17). Furthermore, a poster presented by Russo et al (18), reported an USS patient with homozygosity for the same complex allele as found in the patient described here.…”
Section: Discussionsupporting
confidence: 64%
“…Only 4 of 88 patients receiving plasma prophylaxis experienced TIA/stroke. The fathers of 2 patients died of stroke at ages 39 years 9 and 63 years 10 ; they were assumed to be heterozygous but had not had ADAMTS13 sequencing. This is consistent with the observations that low-normal ADAMTS13 activity increases risk for stroke.…”
Section: Resultsmentioning
confidence: 99%